A strontium silicate-based material that changes color in response to X-rays, and its preparation method and application

By developing rare earth-doped X-ray response discoloration material Sr2SiO4:x%Dy3+, the problem of lack of inorganic materials suitable for X-ray detection in the prior art is solved, and the effect of reversible discoloration of the material under X-ray irradiation is achieved, which is suitable for large-scale production and has rich application scenarios.

CN116395703BActive Publication Date: 2025-03-28JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310399553.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2025-03-28
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

The lack of inorganic materials suitable for X-ray detection in the prior art, and the discovered X-ray photochromic materials cannot return to their initial color, limiting their application.

Method used

A rare earth-doped X-ray responsive discoloration material, specifically Sr2SiO4:x%Dy3+, was developed to turn red by irradiation with X-ray at room temperature and fade to white when heated to above 300°C.

Benefits of technology

Reversible discoloration of materials under X-ray irradiation is achieved, suitable for large-scale production, making up for some gaps in color photochromic materials of X-ray inorganic materials, and has rich application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395703B_ABST
    Figure CN116395703B_ABST
Patent Text Reader

Abstract

The present invention relates to a strontium silicate-based material that changes color in response to X-rays, and its preparation method and application, belonging to the technical field of color-changing materials. At room temperature, it changes color to red when irradiated with X-rays, and fades to white when heated to above 300°C; its chemical structural formula is Sr2SiO4:x%Dy 3+ , wherein x is 0-5. The raw materials used in the present invention are widely available and low in cost, and the preparation process is simple, requiring only ball mill mixing and grinding and sintering, and the operating environment is simple, and no reducing atmosphere protection is required, which is suitable for large-scale production. The material prepared by the present invention changes color when irradiated with X-rays, and fades to white when heated to above 300°C, which fills the partial blank of X-ray inorganic color photochromic materials and has rich application scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a strontium silicate-based material that changes color in response to X-rays and a preparation method and application thereof, belonging to the technical field of color-changing materials. Background Art

[0002] Photochromic materials are a general term for materials that have the photochromic phenomenon. After a period of light exposure, substance A undergoes a chemical reaction, and the sample color and optical state change to another state of substance B. This process is called photochromic phenomenon. In addition, photochromic phenomenon is generally reversible, that is, product B undergoes a corresponding chemical reaction and changes in absorption wavelength under light exposure of another wavelength or other stimulation, and returns to the original state of A. Photochromic phenomenon is a reversible chemical reaction, which has two processes, namely activation process (coloring reaction) and decolorization process (fading reaction). This color change shows the position and intensity change of the visible light absorption peak on the absorption spectrum. Humans have discovered the photochromic phenomenon for more than 100 years.

[0003] Photochromic materials exist in various colors among organic materials, but there are few materials with different colors among inorganic materials. Currently known inorganic photochromic materials mainly include some transition metal oxides, such as tungsten trioxide, molybdenum trioxide, titanium dioxide and vanadium pentoxide. The color change reactions of these typical inorganic photochromic materials are reversible, but most of them only show darkening or graying of the color, and X-ray color-changing materials are rarely studied.

[0004] X-ray sensitive materials used in X-ray detection equipment usually require electronic accessories or multi-step operations to process the signal before useful information can be obtained. Photochromic materials usually exhibit reversible color changes under external stimuli. Assuming that X-rays can be directly "visualized" through color, such as the well-known pH test paper, then X-ray detection will become very convenient and much cheaper. Due to its simple operation, new X-ray sensitive materials that can directly provide the required information are quite promising. If X-rays can stimulate such materials to change color, and they are recyclable and reusable, such materials are the best alternatives, so it is necessary to study X-ray color-changing materials with rich colors.

[0005] Existing technical research shows that there are very few X-ray-induced photochromic materials. The materials that have been discovered include metal-organic complex discrete structure materials, which can undergo photochromic changes under X-ray induction, and some naturally occurring inorganic materials, including mineral stones, etc. Some X-ray photochromic materials cannot return to their original colors.

[0006] Inorganic color-changing materials are the most popular research focus in the field of color-changing materials and have a research history of several decades. However, because the proposed mechanism models are numerous and complex, the academic community can actually only guess the color-changing principle through a few models with relatively high credibility.

[0007] For photochromic materials, rare earth doping is conducive to the introduction of defects, thereby adjusting the color change, and the physical and chemical properties are stable. Therefore, it is very meaningful to study a rare earth doped X-ray chromic material. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a strontium silicate-based material that changes color in response to X-rays and a preparation method and application thereof, wherein the raw materials are widely available and the cost is low, the operation process is simple, and the material is suitable for large-scale production.

[0009] The technical solution of the present invention is a strontium silicate-based material that changes color in response to X-rays. At room temperature, it changes color to red when irradiated with X-rays, and fades to white when heated to above 300°C. Its chemical structural formula is Sr2SiO4:x%Dy 3+ , where x is 0-5.

[0010] Another technical purpose of the present invention is a method for preparing the X-ray responsive color-changing strontium silicate-based material, comprising the following steps:

[0011] S1: SrCO3, SiO2 and Dy2O3 are mixed in anhydrous ethanol in a certain proportion and then ground evenly using a ball mill. The dried and evenly mixed white powder is pressed into tablets to obtain a round tablet-shaped reactant;

[0012] S2: The circular flakes obtained in S1 are sintered at high temperature in an air atmosphere and air-cooled to room temperature to obtain a strontium silicate-based material that changes color in response to X-ray radiation.

[0013] Furthermore, the molar ratio of SrCO3:SiO2 in S1 is specifically 2:1.

[0014] Further, when x=1, the molar ratio of SrCO3:SiO2:Dy2O3 is 2:1:0.01;

[0015] When x = 2, the molar ratio of SrCO3:SiO2:Dy2O3 is 2:1:0.02;

[0016] When x=4, the molar ratio of SrCO3:SiO2:Dy2O3 is 2:1:0.04.

[0017] Furthermore, when the total mass of SrCO3, SiO2 and Dy2O3 is 2g, the amount of anhydrous ethanol is 50-60mL.

[0018] Furthermore, in S1, the tableting pressure is 15-25 MPa, and the tableting time is 1-3 min.

[0019] Furthermore, the rotation speed of the ball mill in S1 is specifically 700-900 r / min, and the ball milling time is specifically 6-8 h.

[0020] Furthermore, the temperature of the high temperature sintering in S2 is specifically 1200-1300°C, the heating rate is 4-6°C / min, and the holding time is 3-4h.

[0021] Another technical purpose of the present invention is to use the strontium silicate-based material that changes color in response to X-rays to detect X-rays.

[0022] Furthermore, the X-ray intensity required for the color change of the strontium silicate-based material is specifically a voltage of 50 kV and a current of 80 μA.

[0023] Sr2SiO4:x%Dy 3+ The phosphor material, under 391nm excitation, emits double-peak blue light at 481nm and 496nm and yellow light at 583nm, with a yellow-blue ratio (Y / B) of 0.827, and the emission intensities of yellow and blue light are similar. However, this fluorescent luminescence requires excitation, and no previous studies have shown that materials with this structure are sensitive to X-rays.

[0024] Beneficial effects of the present invention: The raw materials used in the present invention are widely available and low in cost, the preparation process is simple, only ball mill mixing and grinding and sintering are required, the operating environment is simple, no reducing atmosphere protection is required, and it is suitable for large-scale production. The material prepared by the present invention changes color when irradiated with X-rays, and fades to white when heated to above 300°C, which fills the gap in X-ray inorganic color photochromic materials and has rich application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to make the content of the present invention more easily understood, the present invention is further described in detail below based on specific embodiments and in conjunction with the accompanying drawings, wherein

[0026] Figure 1 X-ray diffraction patterns of materials prepared in Examples 1-4 of the present invention.

[0027] Figure 2 This is a scanning electron microscope image of the material prepared in Example 2 of the present invention.

[0028] Figure 3 This is the element distribution diagram of the material prepared in Example 2 of the present invention.

[0029] Figure 4After 30 minutes of X-ray pre-irradiation, the reflectivity of the material prepared in Example 2 of the present invention was tested twice before and after the color change, and the result was Figure 4 .

[0030] Figure 5 The material prepared in Example 2 of the present invention was pre-irradiated with X-rays for 30 minutes and then heated at 300°C for 2 minutes. The reflectivity was measured twice before and after fading. Figure 5 .

[0031] Figure 6 The material prepared in Example 2 of the present invention was pre-irradiated with X-rays for 30 minutes and then heated at 300°C for 2 minutes. Photos were taken before and after discoloration and after fading. Figure 6 . DETAILED DESCRIPTION

[0032] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0034] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0036] Example 1

[0037] The strontium silicate-based material that changes color in response to X-rays in this embodiment is Sr2SiO4:x%Dy 3+ , x=0, and the preparation steps are:

[0038] S1: SrCO3, SiO2, and Dy2O3 were mixed in anhydrous ethanol in a ratio of 2:1:0 and then ground evenly in a ball mill. The evenly mixed white powder was pressed into tablets to obtain a round tablet-shaped reactant;

[0039] S2: The reactants obtained in S1 are placed in an alumina crucible, placed in a tubular sintering furnace, sintered at a high temperature of 1200-1300°C in an air atmosphere, with a heating rate of 4-6°C / min, a heat preservation time of 3-4h, and air-cooled to room temperature to obtain the temperature-variable color phosphor material Sr2SiO4:x%Dy 3+ , x=0.

[0040] Example 2

[0041] The strontium silicate-based material that changes color in response to X-rays in this embodiment is Sr2SiO4:x%Dy 3+ , x=1, and the preparation steps are:

[0042] S1: SrCO3, SiO2, and Dy2O3 were mixed in anhydrous ethanol in a ratio of 2:1:0.01 and then ground evenly in a ball mill. The evenly mixed white powder was pressed into tablets to obtain a round tablet-shaped reactant;

[0043] S2: The reactants obtained in S1 are placed in an alumina crucible, placed in a tubular sintering furnace, sintered at a high temperature of 1200-1300°C in an air atmosphere, with a heating rate of 4-6°C / min, a heat preservation time of 3-4h, and air-cooled to room temperature to obtain the temperature-variable color phosphor material Sr2SiO4:x%Dy 3+ , x=1.

[0044] Example 3

[0045] The X-ray responsive color-changing strontium silicate-based material of this embodiment is Sr2SiO4:x%Dy3+, x=2, and its preparation steps are as follows:

[0046] S1: SrCO3, SiO2, and Dy2O3 were mixed in anhydrous ethanol in a ratio of 2:1:0.02 and then ground evenly in a ball mill. The evenly mixed white powder was pressed into tablets to obtain a round tablet-shaped reactant;

[0047] S2: The reactants obtained in S1 are placed in an alumina crucible, placed in a tubular sintering furnace, sintered at a high temperature of 1200-1300°C in an air atmosphere, with a heating rate of 4-6°C / min, a heat preservation time of 3-4h, and air-cooled to room temperature to obtain the temperature-variable color phosphor material Sr2SiO4:x%Dy 3+ , x=2.

[0048] Example 4

[0049] The X-ray responsive color-changing strontium silicate-based material of this embodiment is Sr2SiO4:x%Dy3+, x=4, and its preparation steps are as follows:

[0050] S1: SrCO3, SiO2, and Dy2O3 were mixed in anhydrous ethanol in a ratio of 2:1:0.04 and then ground evenly in a ball mill. The evenly mixed white powder was pressed into tablets to obtain a round tablet-shaped reactant;

[0051] S2: The reactants obtained in S1 are placed in an alumina crucible, placed in a tubular sintering furnace, sintered at a high temperature of 1200-1300°C in an air atmosphere, with a heating rate of 4-6°C / min, a heat preservation time of 3-4h, and air-cooled to room temperature to obtain the temperature-variable color phosphor material Sr2SiO4:x%Dy 3+ , x=4.

[0052] Application Examples

[0053] The X-ray response color-changing strontium silicate-based materials obtained in Examples 1-4 were analyzed using an X-ray diffractometer. The results are shown in the attached figure. Figure 1 As shown in the figure, the diffraction pattern is consistent with the standard diffraction pattern of Sr2SiO4 (PDF#38-0271), indicating that doping with dysprosium ions does not cause the formation of new phases, which proves that the strontium silicate-based material obtained in this example is a pure phase of Sr2SiO4 with good chemical stability.

[0054] The morphology of the X-ray responsive color-changing strontium silicate-based material prepared in Example 2 of the present invention was observed under a field emission electron scanning microscope, and it was obtained Figure 2 ,It can be seen from the figure that the sample fired by the solid phase method has ,irregular morphology, larger sample particles, and uneven particle size distribution.

[0055] The elements of the X-ray responsive color-changing strontium silicate-based material prepared in Example 2 of the present invention were analyzed under a field emission electron scanning microscope to obtain Figure 3 ,It can be seen from the figure that each element is evenly distributed in the sample.

[0056] The X-ray responsive color-changing strontium silicate-based material prepared in Example 2 was tested for reflectivity twice before and after color change after X-ray pre-irradiation for 30 minutes. Figure 4 As can be seen from the figure, the ultraviolet reflectivity decreases significantly after 30 minutes of X-ray irradiation, and the reflectivity of the wavelength of 502nm decreases the most, resulting in an increase in the absorption rate, so the color changes to red.

[0057] The X-ray responsive color-changing strontium silicate-based material prepared in Example 2 was pre-irradiated with X-rays for 30 minutes and then heated at 300° C. for 2 minutes. The reflectivity was tested twice, and the result was: Figure 5 As can be seen from the figure, the change in reflectivity before and after is very small, indicating that heating can cause it to fade.

[0058] The X-ray responsive color-changing strontium silicate-based material prepared in Example 2 was pre-irradiated with X-rays for 30 minutes and then heated at 300° C. for 2 minutes. The images were taken respectively. Figure 6 As can be seen from the figure, X-rays turn it red and heating can fade it.

[0059] The above experiments show that the material prepared by the present invention changes color to red when irradiated with X-rays, and fades to white when heated to above 300°C, filling in some gaps in X-ray inorganic color photochromic materials and having rich application scenarios.

[0060] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of a strontium silicate-based material that changes color in response to X-ray radiation, characterized in that: Its chemical structure is Sr2SiO4:x%Dy 3+ , where x is 0-5; it is applied to detect X-rays; at room temperature, it changes color to red when irradiated with X-rays, and fades to white when heated above 300°C.

2. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 1, characterized in that: The X-ray intensity required for the color change of strontium silicate-based materials is specifically a voltage of 50 kV and a current of 80 μA.

3. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 1, characterized in that: The method for preparing the X-ray responsive color-changing strontium silicate-based material comprises the following steps: S1: SrCO3, SiO2 and Dy2O3 are mixed in anhydrous ethanol in a certain proportion and ground evenly using a ball mill; the dried and evenly mixed white powder is pressed into tablets to obtain a round tablet-shaped reactant; S2: The circular flakes obtained in S1 are sintered at high temperature in an air atmosphere and air-cooled to room temperature to obtain a strontium silicate-based material that changes color in response to X-ray radiation.

4. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 3, characterized in that: The specific molar ratio of SrCO3:SiO2 in S1 is 2:

1.

5. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 4, characterized in that: When x = 1, the molar ratio of SrCO3:SiO2:Dy2O3 is 2:1:0.01; When x = 2, the molar ratio of SrCO3:SiO2:Dy2O3 is 2:1:0.02; When x=4, the molar ratio of SrCO3:SiO2:Dy2O3 is 2:1:0.

04.

6. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 3, characterized in that: When the total mass of the SrCO3, SiO2 and Dy2O3 is 2g, the amount of anhydrous ethanol is 50-60mL.

7. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 3, characterized in that: The tableting pressure in S1 is 15-25 MPa, and the tableting time is 1-3 min.

8. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 3, characterized in that: The rotation speed of the ball mill in S1 is specifically 700-900 r / min, and the ball milling time is specifically 6-8 h.

9. The use of the X-ray responsive color-changing strontium silicate-based material as claimed in claim 3, characterized in that: The temperature of the high temperature sintering in S2 is specifically 1200-1300°C, the heating rate is 4-6°C / min, and the holding time is 3-4h.

Citation Information

Patent Citations

  • Orange-yellow long afterglow phosphor

    CN104592989A

  • Near-infrared long afterglow material as well as preparation method and application thereof

    CN115820245A